Baseline hydro-geochemical characteristics of groundwater in Abu Ali watershed (Northern Lebanon) - Rachad Al Haj; Mohammad Merheb; Jalal Halwani; Baghdad Ouddane (Journal of Hydrology: Regional Studies)
Study region: Abu Ali’s basin in northern Lebanon. Study focus: This study aims to analyze the hydrogeochemical characteristics of Abu Ali’s groundwater. Sixty-five groundwater samples were collected during the wet and dry seasons of 2019 and 2020. The following physicochemical parameters were measured in the field: temperature, pH, total dissolved solids (TDS), and electrical conductivity (EC). The concentrations of nine major ions—Ca²⁺, Mg²⁺, Na⁺, K⁺, HCO₃⁻, Cl⁻, SO₄²⁻, NO₃⁻, and PO₄³ ⁻—were determined using titration, colorimetric and potentiometric methods, and inductively coupled plasma optical emission spectroscopy (ICP-OES). The data were analyzed using hydrogeochemical plots and multivariate analysis. New insights for the region: Results show that the dominant hydrochemical facies are Ca-HCO₃ and Ca-Mg-HCO₃, while rock-water interaction is the primary geochemical process. Carbonate weathering is the main source of ions. Additionally, cluster analysis and principal component analysis (PCA) divide the samples into four groups. The first group is characterized by high-altitude springs with low residence times. Another group, at slightly lower altitudes, shares the same geological formation (Cenomanian-Turonian) and includes a large number of wells. The remaining two groups consist mostly of wells exploiting the Miocene aquifer at lower altitudes, where agricultural activity is more intense. Finally, this study provides a preliminary assessment of Abu Ali’s groundwater hydrogeochemistry, and further investigations are certainly needed.